High-throughput sequencing and characterization of potentially pathogenic fungi from the vaginal mycobiome of giant panda (Ailuropoda melanoleuca) in estrus and non-estrus - Ma, Xiaoping; Liu, Zhen; Yue, Chanjuan; Wang, Siwen; Li, Xinni; Wang, Chengdong; Ling, Shanshan; Wang, Ya; Liu, Songrui; Gu, Yu (Frontiers in Microbiology, 2024)
The giant panda (Ailuropoda melanoleuca) reproduction is of worldwide attention, and the vaginal microbiome is one of the most important factors affecting the reproductive rate of giant pandas. The aim of this study is to investigate the diversity of vaginal mycobiota structure, and potential pathogenic fungi in female giant pandas during estrus and non-estrus.Methods: This study combined with high-throughput sequencing and laboratory testing to compare the diversity of the vaginal mycobiota in giant pandas during estrus and non-estrus, and to investigate the presence of potentially pathogenic fungi.Potentially pathogenic fungi were studied in mice to explore their pathogenicity.The results revealed that during estrus, the vaginal secretions of giant pandas play a crucial role in fungal colonization. Moreover, the diversity of the vaginal mycobiota is reduced and specificity is enhanced. The abundance of Trichosporon and Cutaneotrichosporon in the vaginal mycobiota of giant pandas during estrus was significantly higher than that during non-estrus periods.Apiotrichum and Cutaneotrichosporon were considered the most important genera, and they primarily originate from the environment owing to marking behavior exhibited during the estrous period of giant pandas. Trichosporon is considered a resident mycobiota of the vagina and is an important pathogen that causes infection when immune system is suppressed. Potentially pathogenic fungi were further isolated and identified from the vaginal secretions of giant pandas during estrus, and seven strains of Apiotrichum (A. brassicae), one strain of Cutaneotrichosporon (C. moniliiforme), and nine strains of Trichosporon (two strains of T. asteroides, one strain of T. inkin, one strain of T. insectorum, and five strains of T. japonicum) were identified. Pathogenicity results showed that T. asteroides was the most pathogenic strain, as it is associated with extensive connective tissue replacement and inflammatory cell infiltration in both liver and kidney tissues. The results of this study improve our understanding of the diversity of the vaginal fungi present in giant pandas and will significantly contribute to improving the reproductive health of giant pandas in the future.